Following the Formula in Beowulf, Örvar-Odds saga, and Tolkien - Fox, Michael. author. (orcid)0009-0003-1743-1405 Link aut Link
XIV, 250 p. 2 illus.
Keywords: Following the Formula in Beowulf, Örvar-Odds saga, and Tolkien proposes that Beowulf was composed according to a formula. Michael Fox imagines the process that generated the poem and provides a model for reading it, extending this model to investigate formula in a half-line, a fitt, a digression, and a story-pattern or folktale, including the Old-Norse Icelandic Örvar-Odds saga. Fox also explores how J. R. R. Tolkien used the same formula to write Sellic Spell and The Hobbit. This investigation uncovers relationships between oral and literate composition, between mechanistic composition and author, and between listening and reading audiences, arguing for a contemporary relevance for Beowulf in thinking about the creative process.